An aspect of personality disorder in substance use disorder - Sukma, Dwi Ayu Anggaraeni; Ardani, I. Gusti Ayu Indah; Wahyuni, Anak Ayu Sri (International Journal of Research in Medical Sciences, 2022)
Substance use disorder (SUD) remains a health problem for a long time and the number of substance abuse was relatively the same every year. The prevalence of substance abuse in Indonesia in 2011 is about 2.23%, it was slightly decreased in 2014 become 2.18% and 1.77% in 2017. However, the prevalence was increased again in 2019 become 1.80%. Previous studies had shown a strong association between personality disorder (PD) and SUD. The result of the national comorbidity survey replication by Glantz et al in the United States (US) found that patients with PD tend to experience SUD (odd ratio=4.9). All types of PD had been reported in the patients with SUD, but antisocial and borderline personality disorder was the most commonly found. Antisocial, borderline, and paranoid personalities had a positive association with SUD, meanwhile, obsessive-compulsive personalities had a negative association with SUD.